Interest Rate Determination in Lebanon - Poddar, Tushar; Goswami, Mangal; Icaza, Victor Echevarria; Sole, Juan. (Washington, D.C. : International Monetary Fund, 2006)
This paper seeks to understand how interest rates are formed in Lebanon, by focusing on the pass-through from benchmark rates, prevailing liquidity conditions, and the main characteristics of the Lebanese economy, notably its open capital account, fixed exchange rate, high government borrowing requirement, large public debt, and high degree of deposit dollarization. We find that international interest rates are an important element in the determination of interest rates in Lebanon. In particular, the pass-through of global benchmark rates to interest rates on sovereign bonds is about 70 percent. The less-than-complete pass-through could be attributed to a home-bias effect reflecting a relatively stable and dedicated investor base. The study also shows that interest rates in Lebanon are affected by liquidity conditions as well as perceived sovereign risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet